Characterization of Histone H3 Gene Family Reveals That GmHH3-3 is Associated With Higher Seed Weight in Glycine max - Fatima, Chahat; Tahir, Muhammad Hammad Nadeem; Ikram, Rao Muhammad; Khan, Zulqurnain; Sajjad, Muhammad; Qanmber, Ghulam; Darwish, Essam; Geng, Zhide; Xiangkuo, Gao; Ur Rehman, Shoaib (Frontiers in Genetics, 2022)
Main function of Histone protein is to provide support to the structure of chromosomes. It helps in binding a long thread of DNA into a more condensed shape to fit into the nucleus. From histone variants, histone H3 (HH3) plays crucial roles in plant growth development. Characterization of histones has been not reported in Glycine max till now. The objective of this study is to characterize HH3 gene family for molecular breeding of G. max. In this study 17 HH3 members in G. max were identified by doing local BLASTp using HH3 members from Arabidopsis as a query. Phylogenetic analysis classified HH3 genes in seven clades. Sequence logo analysis among Arabidopsis thaliana, Oryza sativa and Glycine max showed higher level of similarity in amino acids. Further, conserveness of G. max HH3 genes was also confirmed by Gene Structure Display. Ten paralogous gene pairs were identified in GmHH3 genes in Glycine max genome by doing collinearity analysis. G. max HH3 genes have experienced strong purifying selection pressure, with limited functional divergence originating from segmental and whole-genome duplication, as evidenced by the Ka/Ks ratios. KASP marker was developed of GmHH3-3 gene. Genotyping was performed on forty-six G. max genotypes. This differentiation was based upon presence of either GmHH3-3-C or GmHH3-3-T allele in CDS region. The results showed that G. max accessions containing GmHH3-3-T allele at respective locus showed higher thousand grain weight as compared to those accessions that contain GmHH3-3-C allele. This research provides the basic information to further decipher the function of HH3 in soybean.